Adhesion G Protein-Coupled Receptor Gpr126 (Adgrg6) Expression Profiling in Diseased Mouse, Rat, and Human Kidneys - Kösters, Peter; Cazorla Vázquez, Salvador; Krüger, René; Daniel, Christoph; Vonbrunn, Eva; Amann, Kerstin Ute; Engel, Felix (Cells, 2024)
Uncovering the function of understudied G protein-coupled receptors (GPCRs) provides a wealth of untapped therapeutic potential. The poorly understood adhesion GPCR Gpr126 (Adgrg6) is widely expressed in developing kidneys. In adulthood, Gpr126 expression is enriched in parietal epithelial cells (PECs) and epithelial cells of the collecting duct and urothelium. Whether Gpr126 plays a role in kidney disease remains unclear. Here, we characterized Gpr126 expression in diseased kidneys in mice, rats, and humans. RT-PCR data show that Gpr126 expression is altered in kidney disease. A quantitative RNAscope® analysis utilizing cell type-specific markers revealed that Gpr126 expression upon tubular damage is mainly increased in cell types expressing Gpr126 under healthy conditions as well as in cells of the distal and proximal tubules. Upon glomerular damage, an increase was mainly detected in PECs. Notably, Gpr126 expression was upregulated in an ischemia/reperfusion model within hours, while upregulation in a glomerular damage model was only detected after weeks. An analysis of kidney microarray data from patients with lupus nephritis, IgA nephropathy, focal segmental glomerulosclerosis (FSGS), hypertension, and diabetes as well as single-cell RNA-seq data from kidneys of patients with acute kidney injury and chronic kidney disease indicates that GPR126 expression is also altered in human kidney disease. In patients with FSGS, an RNAscope® analysis showed that GPR126 mRNA is upregulated in PECs belonging to FSGS lesions and proximal tubules. Collectively, we provide detailed insights into Gpr126 expression in kidney disease, indicating that GPR126 is a potential therapeutic target.
CRIS-Team Scopus Importer:2024-05-31
Keywords: adhesion GPCR; collecting duct; focal segmental glomerulosclerosis; Gpr126; human; kidney disease; parietal epithelial cell; RNAscope; urothelium

Allograft infiltration and meningoencephalitis by SARS-CoV-2 in a pancreas-kidney transplant recipient - Westhoff, Timm H.; Seibert, Felix S.; Bauer, Frederic; Stervbo, Ulrik; Anft, Moritz; Doevelaar, Adrian A. N.; Rohn, Benjamin J.; Winnekendonk, Guido; Dittmer, Ulf; Schenker, Peter; Vonbrunn, Eva; Amann, Kerstin Ute; et al. (American Journal of Transplantation, 2020)
Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) preferentially affects epithelia of the upper and lower respiratory tract. Thus, impairment of kidney function has been primarily attributed until now to secondary effects such as cytokine release or fluid balance disturbances. We provide evidence that SARS-CoV-2 can directly infiltrate a kidney allograft. A 69-year-old male, who underwent pancreas-kidney transplantation 13 years previously, presented to our hospital with coronavirus disease 2019 (COVID-19) pneumonia and impaired pancreas and kidney allograft function. Kidney biopsy was performed showing tubular damage and an interstitial mononuclear cell infiltrate. Reverse transcriptase polymerase chain reaction from the biopsy specimen was positive for SARS-CoV-2. In-situ hybridization revealed SARS-CoV-2 RNA in tubular cells and the interstitium. Subsequently, he had 2 convulsive seizures. Magnetic resonance tomography suggested meningoencephalitis, which was confirmed by SARS-CoV-2 RNA transcripts in the cerebrospinal fluid. The patient had COVID-19 pneumonia, meningoencephalitis, and nephritis. SARS-CoV-2 binds to its target cells through angiotensin-converting enzyme 2, which is expressed in a broad variety of tissues including the lung, brain, and kidney. SARS-CoV-2 thereby shares features with other human coronaviruses including SARS-CoV that were identified as pathogens beyond the respiratory tract as well. The present case should provide awareness that extrapulmonary symptoms in COVID-19 may be attributable to viral infiltration of diverse organs.
CRIS-Team Scopus Importer:2020-09-11

Can Gene Expression Analysis in Zero-Time Biopsies Predict Kidney Transplant Rejection? - Vonbrunn, Eva; Angeloni, Miriam; Büttner-Herold, Maike; Müller-Deile, Janina; Heller, Katharina M.; Bleich, Erik; Söllner, Stefan; Amann, Kerstin Ute; Ferrazzi, Fulvia; Daniel, Christoph (Frontiers in Medicine, 2022)
Zero-time biopsies are taken to determine the quality of the donor organ at the time of transplantation. Histological analyses alone have so far not been able to identify parameters that allow the prediction of subsequent rejection episodes or graft survival. This study investigated whether gene expression analyses of zero-time biopsies might support this prediction. Using a well-characterized cohort of 26 zero-time biopsies from renal transplant patients that include 4 living donor (LD) and 22 deceased donor (DD) biopsies that later developed no rejection (Ctrl, n = 7), delayed graft function (DGF, n = 4), cellular (T-cell mediated rejection; TCMR, n = 8), or antibody-mediated rejection (ABMR, n = 7), we analyzed gene expression profiles for different types of subsequent renal transplant complication. To this end, RNA was isolated from formalin-fixed, paraffin-embedded (FFPE) sections and gene expression profiles were quantified. Results were correlated with transplant data and B-cell, and plasma cell infiltration was assessed by immunofluorescence microscopy. Both principal component analysis and clustering analysis of gene expression data revealed marked separation between LDs and DDs. Differential expression analysis identified 185 significant differentially expressed genes (adjusted p < 0.05). The expression of 68% of these genes significantly correlated with cold ischemia time (CIT). Furthermore, immunoglobulins were differentially expressed in zero-time biopsies from transplants later developing rejection (TCMR + ABMR) compared to non-rejected (Ctrl + DGF) transplants. In addition, immunoglobulin expression did not correlate with CIT but was increased in transplants with previous acute renal failure (ARF). In conclusion, gene expression profiles in zero-time biopsies derived from LDs are markedly different from those of DDs. Pre-transplant ARF increased immunoglobulin expression, which might be involved in triggering later rejection events. However, these findings must be confirmed in larger cohorts and the role of early immunoglobulin upregulation in zero-biopsies needs further clarification.
CRIS-Team Scopus Importer:2022-04-29
Keywords: inflammation; kidney transplantation; mRNA expression; outcome; zero-time biopsy

Complement Activation in Kidneys of Patients With COVID-19 - Pfister, Frederick; Vonbrunn, Eva; Ries, Tajana; Jäck, Hans-Martin; Überla, Klaus; Lochnit, Günter; Sheriff, Ahmed; Herrmann, Martin; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2021)
Most patients who became critically ill following infection with COVID-19 develop severe acute respiratory syndrome (SARS) attributed to a maladaptive or inadequate immune response. The complement system is an important component of the innate immune system that is involved in the opsonization of viruses but also in triggering further immune cell responses. Complement activation was seen in plasma adsorber material that clogged during the treatment of critically ill patients with COVID-19. Apart from the lung, the kidney is the second most common organ affected by COVID-19. Using immunohistochemistry for complement factors C1q, MASP-2, C3c, C3d, C4d, and C5b-9 we investigated the involvement of the complement system in six kidney biopsies with acute kidney failure in different clinical settings and three kidneys from autopsy material of patients with COVID-19. Renal tissue was analyzed for signs of renal injury by detection of thrombus formation using CD61, endothelial cell rarefaction using the marker E-26 transformation specific-related gene (ERG-) and proliferation using proliferating cell nuclear antigen (PCNA)-staining. SARS-CoV-2 was detected by in situ hybridization and immunohistochemistry. Biopsies from patients with hemolytic uremic syndrome (HUS, n = 5), severe acute tubular injury (ATI, n = 7), zero biopsies with disseminated intravascular coagulation (DIC, n = 7) and 1 year protocol biopsies from renal transplants (Ctrl, n = 7) served as controls. In the material clogging plasma adsorbers used for extracorporeal therapy of patients with COVID-19 C3 was the dominant protein but collectin 11 and MASP-2 were also identified. SARS-CoV-2 was sporadically present in varying numbers in some biopsies from patients with COVID-19. The highest frequency of CD61-positive platelets was found in peritubular capillaries and arteries of COVID-19 infected renal specimens as compared to all controls. Apart from COVID-19 specimens, MASP-2 was detected in glomeruli with DIC and ATI. In contrast, the classical pathway (i.e. C1q) was hardly seen in COVID-19 biopsies. Both C3 cleavage products C3c and C3d were strongly detected in renal arteries but also occurs in glomerular capillaries of COVID-19 biopsies, while tubular C3d was stronger than C3c in biopsies from COVID-19 patients. The membrane attack complex C5b-9, demonstrating terminal pathway activation, was predominantly deposited in COVID-19 biopsies in peritubular capillaries, renal arterioles, and tubular basement membrane with similar or even higher frequency compared to controls. In conclusion, various complement pathways were activated in COVID-19 kidneys, the lectin pathway mainly in peritubular capillaries and in part the classical pathway in renal arteries whereas the alternative pathway seem to be crucial for tubular complement activation. Therefore, activation of the complement system might be involved in the worsening of renal injury. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: complement—immunological term; COVID-19; endothelial injury; kidney; lectin pathway activation

Complement Inhibition in Kidney Transplantation: Where Are We Now? - Vonbrunn, Eva; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Biodrugs, 2022)
Kidney transplantation is a life-saving strategy for patients with end-stage renal disease. Although progress has been made in the field of transplantation medicine in recent decades in terms of surgical techniques and immunosuppression, long-term organ survival remains a challenge. Also, for reasons of organ shortage, there is an unmet need for new therapeutic approaches to improve the long-term survival of transplants. There is increasing evidence that the complement system plays a crucial role in various pathological events after transplantation, including ischemia/reperfusion injury as well as rejection episodes. The complement system is part of the innate immune system and plays a crucial role in the defense against pathogens but is also involved in tissue homeostasis. However, the tightly regulated complement system can become dysregulated or activated by non-infectious stimuli, then targeting the organism’s own cells and leading to inflammatory tissue damage that exacerbates injury. In this review, we will highlight the role of the complement system after transplantation and discuss ongoing and potential therapeutic approaches.
CRIS-Team Scopus Importer:2022-12-23

COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

Die Komplementkaskade in der Nierenpathologie - Vonbrunn, Eva; Daniel, Christoph (Die Pathologie, 2024)
The complement cascade comprises a variety of soluble and cell surface proteins and is an important component of the innate immune system. When the cascade is triggered by any of the three activation pathways, the complement system rapidly produces large amounts of protein fragments that are potent mediators of inflammatory, vasoactive, and metabolic responses. All activation pathways lead to the terminal complement cascade with the formation of the membrane attack complex, which lyses cells by forming membrane pores. Although the complement system is essential for pathogen defense and homeostasis, excessive or uncontrolled activation can lead to tissue damage. Recent research shows that the complement system is activated in almost all kidney diseases, even those not traditionally considered immune-mediated. In directly complement-mediated kidney diseases, complement factors or regulators are defective, afunctional or inactivated by antibodies. In many other renal diseases, the complement system is activated secondarily as a result of renal damage and is therefore involved in the pathogenesis of the disease, but is not the trigger. The detection of complement deposits is also used to diagnose kidney disease. This review describes the structure of the complement system and the effects of its dysregulation as a cause and modulator of renal disease.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Antibodies; C3G; Immune system; Lectin; Microangiopathy

Hypertension in Living Kidney Donors Has No Effect on Complement Activation and Fibrosis - Wagner, Nicola; Angeloni, Miriam; Ferrazzi, Fulvia; Müller-Deile, Janina; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph; Vonbrunn, Eva (Kidney & Blood Pressure Research, 2025)
Introduction: In the past, elevated blood pressure was considered an exclusion criterion for living kidney donation because of concerns about premature kidney failure. Hypertension leads to complement deposits and renal fibrosis in the kidney. Therefore, the aim of this study was to investigate whether increased complement deposits and fibrosis can be observed in grafts of hypertensive compared to normotensive living donors. Methods: Zero-time renal biopsies from 238 living donors (52 hypertensive) and the corresponding 1-year protocol biopsies were examined for complement deposits of C1q, C3c, and MASP-2. Findings were compared to kidney biopsies from patients with hypertensive nephropathy. Further, renal fibrosis was visualized by Sirius red staining, scored semiquantitatively, and compared to biopsies from deceased donors and kidneys with hypertensive nephropathy. Additionally, zero-time biopsies from hypertensive (n = 6) and normotensive (n = 5) living donors were analyzed for expression of fibrosis-associated genes by multiplex mRNA analysis and compared to zero-time biopsies (n = 6) from deceased donors. Results: In all zero-time biopsies from living donors, complement deposits were minimal for C1q, C3c, and MASP-2 compared to samples with hypertensive nephropathy, regardless of whether the donor was hypertensive or normotensive. In 1-year protocol biopsies, complement deposits were unchanged, while renal fibrosis was slightly but not significantly increased in hypertensive compared to normotensive living donors. Gene expression data showed that the 11 zero-time biopsies from hypertensive and normotensive living donors clustered together and were clearly separated from the deceased donor biopsies. Conclusion: The use of kidneys from hypertensive living donors appears to have no or little effect on renal complement deposits and fibrosis 1 year after transplantation.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Complement system; Hypertension; Kidney transplantation; Living kidney donor; Renal fibrosis

Lessons for the clinical nephrologist: recurrence of nephrotic syndrome induced by SARS-CoV-2 - Doevelaar, Adrian A.N.; Hölzer, Bodo; Seibert, Felix S.; Bauer, Frederic; Stervbo, Ulrik; Rohn, Benjamin J.; Zgoura, Panagiota; Schenker, Peter; Vonbrunn, Eva; Amann, Kerstin Ute; Viebahn, Richard; Babel, Nina; et al. (Journal of Nephrology, 2020)
SARS-CoV-2 is characterized by a multiorgan tropism including the kidneys. Recent autopsy series indicated that SARS-CoV-2 can infect both tubular and glomerular cells. Whereas tubular cell infiltration may contribute to acute kidney injury, data on a potential clinical correlative to glomerular affection is rare. We describe the first case of nephrotic syndrome in the context of COVID-19 in a renal transplant recipient. A 35 year old male patient received a kidney allograft for primary focal segmental glomerulosclerosis (FSGS). Three months posttransplant a recurrence of podocytopathy was successfully managed by plasma exchange, ivIG, and a conversion from tacrolimus to belatacept (initial proteinuria > 6 g/l decreased to 169 mg/l). Six weeks later he was tested positive for SARS-CoV-2 and developed a second increase of proteinuria (5.6 g/l). Renal allograft biopsy revealed diffuse podocyte effacement and was positive for SARS-CoV-2 in RNA in-situ hybridation indicating a SARS-CoV-2 associated recurrence of podocytopathy. Noteworthy, nephrotic proteinuria resolved spontaneously after recovering from COVID-19. The present case expands the spectrum of renal involvement in COVID-19 from acute tubular injury to podocytopathy in renal transplant recipients. Thus, it may be wise to test for SARS-CoV-2 prior to initiation of immunosuppression in new onset glomerulopathy during the pandemic.
CRIS-Team Scopus Importer:2020-09-18
Keywords: COVID-19; Podocytopathy; SARS-CoV-2

Macrophage-Induced Pro-Fibrotic Gene Expression in Tubular Cells after Ischemia/Reperfusion Is Paralleled but Not Directly Mediated by C5a/C5aR1 Signaling - Bleich, Erik; Vonbrunn, Eva; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Life, 2024)
Ischemia/reperfusion (I/R) is inevitable during kidney transplantation and causes acute kidney injury (AKI), which affects immediate outcome and leads to chronic changes such as fibrotic remodeling of the graft. We investigated pro-fibrotic signaling after I/R, focusing on the complement component and receptor C5a/C5aR1 and macrophage/tubule crosstalk. Male Dark Agouti rats were subjected to I/R and their kidneys were harvested 10 min, 6 h, 24 h, 3 days, 5 days and 8 weeks after reperfusion. The development of renal fibrosis was assessed by the detection of Vimentin (VIM), α-smooth muscle actin (α-SMA) and collagen by immunohistochemistry and Sirius Red staining, respectively. The characterization of C5a/C5aR1 activity and C5aR1+ cells was performed by multiplex mRNA analysis, ELISA, immunofluorescence flow cytometry and in situ hybridization in animal models and cell culture analyses. In the cell culture experiments, we focused on macrophage/tubule cell crosstalk in co-culture experiments and mimicked in vivo conditions by hypoxia/reoxygenation and supplementation with C5a. Already 6–24 h after the induction of I/R in the rat model, C5a concentration in the plasma was significantly increased compared to the control. The matrix components VIM and α-SMA peaked on day 5 and declined after 8 weeks, when an increase in collagen was detected using Sirius Red. In contrast to early I/R-induced C5a activation, renal C5ar1 expression was maximal at day 5 and C5 expression increased until week 8, indicating that the renal upregulation of expression is not required for early complement activation. C5aR1 mRNA was detected in neutrophils and macrophages, but not in proximal tubular cells in the injured kidneys. The macrophage/tubular cell co-culture experiments showed that macrophages were mainly responsible for the increased expression of fibrosis-associated genes in tubule cells (ACTA2, VIM, SNAI1, TGFB1 and FGF-2), and hypoxia/reoxygenation had a partially enhancing effect. A direct pro-fibrotic effect of C5a was not observed. Increased TGF-ß levels were dependent on the differentiation of macrophages to the M2 subtype. In conclusion, the early activation of mesenchymal markers in tubular epithelial cells leads to long-term fibrotic remodeling characterized by VIM expression and driven by TGF-ß-dependent macrophage/tubular crosstalk. The chemoattractive properties of complement C5a may contribute to the recruitment of pro-fibrotic macrophages.
CRIS-Team Scopus Importer:2024-09-06
Keywords: complement C5a; fibrosis; ischemia/reperfusion; macrophage/tubular crosstalk

Multiplex gene analysis reveals T-cell and antibody-mediated rejection-specific upregulation of complement in renal transplants - Vonbrunn, Eva; Ries, Tajana; Söllner, Stefan; Müller-Deile, Janina; Büttner, Maike; Amann, Kerstin Ute; Daniel, Christoph (Scientific Reports, 2021)
In renal transplantation, complement is involved in ischemia reperfusion injury, graft rejection and dysfunction. However, it is still unclear how induction of complement and its activation are initiated. Using allograft biopsies of a well-characterized cohort of 28 renal transplant patients with no rejection (Ctrl), delayed graft function (DGF), acute T-cell-mediated (TCMR) or antibody-mediated rejection (ABMR) we analyzed differences in complement reaction. For that mRNA was isolated from FFPE sections, quantified with a multiplex gene expression panel and correlated with transplant conditions and follow-up of patients. Additionally, inflammatory cells were quantified by multiplex immunohistochemistry. In allograft biopsies with TCMR and ABMR gene expression of C1QB was 2-4 fold elevated compared to Ctrl. In TCMR biopsies, mRNA counts of several complement-related genes including C1S, C3, CFB and complement regulators CFH, CR1 and SERPING1 were significantly increased compared to Ctrl. Interestingly, expression levels of about 75% of the analyzed complement related genes correlated with cold ischemia time (CIT) and markers of inflammation. In conclusion, this study suggest an important role of complement in transplant pathology which seems to be at least in part triggered by CIT. Multiplex mRNA analysis might be a useful method to refine diagnosis and explore new pathways involved in rejection.
CRIS-Team Scopus Importer:2021-08-13

Relevance of glomerular c4d deposition in pediatric patients with henoch-schönlein purpura compared to IgA nephritis - Benz, Kerstin; Ferrazzi, Fulvia; Galiano, Matthias; Sauerstein, Katja; Vonbrunn, Eva; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute (Journal of Nephropathology, 2021)
Introduction: IgA nephropathy (IgAN) is the most common primary glomerulonephritis (GN) in western countries and Henoch-Schönlein purpura nephritis (HSPN) is the most common form of vasculitis in childhood. Renal biopsy findings in both nephropathies are often similar and are characterized by mesangioproliferative GN with mesangial or mesangiocapillary IgA and C3c deposits. Objectives: The aim of this study was to investigate the significance of glomerular C4d-deposition as a discriminating factor between pediatric HSPN and IgAN. Patients and Methods: We retrospectively analyzed patient records and renal biopsies from 53 pediatric patients from one single center with a median age of 10.5 years (range 2.3-18 years). Twenty-two patients suffered from IgAN and 31 from HSPN. Work-up of all renal biopsies was performed using standard protocols including immunohistochemistry for C4d. Results: Pediatric IgAN patients presented significantly more often with gross hematuria, higher serum creatinine, lower glomerular filtration rate, lower serum C3 and proteinuria and on histology less endocapillary hypercellularity compared to HSPN patients. However, the rate of glomerular C4d-positivity was not different between IgAN (36%) and HSPN (42%). Comparing all cases with positive versus negative glomerular C4d-staining, pediatric patients with glomerular C4d-positivity showed significantly lesser gross hematuria and received significantly more often cyclophosphamide. This was in line with a tendency towards more proteinuria, hypertension and renal insufficiency at last follow-up in C4d-positive compared to C4d-negative patients. Conclusion: In conclusion, in our monocentric study glomerular C4d does not differ between pediatric HSPN and IgAN, but was associated with a tendency to a more severe course of the disease that needs to be confirmed in larger multicentric studies.
CRIS-Team Scopus Importer:2021-01-22
Keywords: C4d staining; Glomerulonephritis; Henoch-Schönlein purpura; IgA nephritis; IgA vasculitis; Pediatric nephrology

Serum Uromodulin as early marker for ischemic acute kidney injury and nephron loss: association with kidney tissue distribution pattern - Vonbrunn, Eva; Ebert, Nadja; Cordasic, Nada; Amann, Kerstin Ute; Büttner, Anke; Büttner-Herold, Maike; Scherberich, Jürgen E.; Daniel, Christoph (Journal of Translational Medicine, 2025)
Background: Uromodulin (UMOD) is expressed in kidneys and is mainly excreted in the urine, although a smaller amount is also released into the serum. Here, we investigated UMOD in acute kidney injury (AKI), with particular focus on the utility of serum UMOD as marker for nephron loss. Methods: Blood and kidney samples were collected 6 h, 24 h, 3 days and 8 weeks after ischemia/reperfusion (I/R) in a rat model. To investigate the impact of nephron number on UMOD levels, sera and tissue from healthy, uninephrectomized (Unx) and 5/6-nephrectomized (Snx) rats were analyzed. Histological changes, kidney function and cell damage were evaluated and serum UMOD, Umod mRNA expression and distribution of UMOD protein in the kidney were examined. Results: In AKI, kidney function was markedly impaired 24 h after I/R, while kidney injury and serum UMOD was increased transiently. Simultaneously, the amount of UMOD-positive kidney cells rapidly decreased 24 h after I/R compared to healthy kidneys, and mRNA expression of Umod was lowest on days 1–3 after I/R. Serum UMOD correlated with nephron number showing the highest levels in healthy rats, which were reduced after Unx and further reduced after Snx. Conclusion: In an AKI model with severe tubular damage, a transient increase in UMOD serum levels in parallel with loss of UMOD-positive cells suggests temporary release of UMOD from destroyed tubular cells into the blood. Serum UMOD appears to be not only a marker of chronic renal failure but also of acute loss of functional and cellular integrity of kidney epithelia in AKI.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Acute kidney injury; Ischemia/reperfusion; Nephron loss; Tamm-Horsfall protein; Uromodulin

Significance of Glomerular Immune Reactivity in Time Zero Biopsies for Allograft Survival Beyond IgA - Vonbrunn, Eva; Serikova, Sofya; Daniel, Christoph; Amann, Kerstin Ute; Schödel, Johannes; Buchholz, Björn; Ferrazzi, Fulvia; Heller, Katharina M.; Apel, Hendrik; Büttner-Herold, Maike (Frontiers in Medicine, 2021)
The quality of a renal transplant can influence the clinical course after transplantation. Glomerular immune reactivity in renal transplants has previously been described, focusing particularly on IgA, and has been shown to disappear in most cases without affecting the outcome. Here, we describe a cohort of time zero biopsies with regard to glomerular immune reactivity and implications for histomorphology and follow-up. 204 Time zero biopsies were analyzed by immunohistochemistry for glomerular immune reactivity. Time zero and 1-year biopsies were evaluated for histomorphological changes, which, together with clinical and follow-up data, were assessed for associations with glomerular immune profiles. Nearly half of the analyzed time zero biopsies showed glomerular immune reactivity with mesangial C3 being the most common (32.9%), followed by IgA (13.7%) and fullhouse patterns (6.9%). Strong C3 deposits (C3high) were only observed in deceased transplants. In the majority of cases immune reactivity was undetectable in follow-up biopsies and had no adverse effect on transplant function in follow-up of 5 years. In kidney pairs transplanted to different recipients a strong concordance of immune profiles in both kidneys was observed. Moreover, an association of male donor sex and deceased donor transplantation with the presence of immune reactivity was observed. In conclusion, glomerular immune reactivity is a very frequent finding in time zero biopsies, which seems to be determined by donor parameters including male sex and deceased donor transplants. It had no adverse impact on transplant function in 5-year follow-up. Glomerular immune reactivity in time zero biopsies, therefore, does not appear to indicate an inferior quality of the transplant.
CRIS-Team WoS Importer:2021-04-30
Keywords: complement; renal tranplantation; time zero biopsy; transplant quality; immune reactivity

The microbial metabolite desaminotyrosine protects against graft-versus-host disease via mTORC1 and STING-dependent intestinal regeneration - Göttert, Sascha; Thiele Orberg, Erik; Fan, Kaiji; Heinrich, Paul; Matthe, Diana; Khalid, Omer; Klostermeier, Lena; Suriano, Chiara; Strieder, Nicholas; Gebhard, Claudia; Vonbrunn, Eva; Mamilos, Andreas; et al. (Nature Communications, 2025)
Changes in the intestinal microbiome and microbiota-derived metabolites predict clinical outcomes after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Here, we report that desaminotyrosine (DAT), a product of bacterial flavonoid metabolism, correlates with improved overall survival and reduced relapse rates in patients receiving allo-HSCT. In preclinical mouse models, treatment with synthetic DAT prevents graft-versus-host disease by protecting the intestinal barrier and promoting intestinal regeneration and contributes to graft-vs.-leukemia responses. DAT´s beneficial effects on intestinal regeneration remain effective despite broad-spectrum antibiotics-induced dysbiosis, also when administered by fecal microbiota transfer with flavonoid-degrading F. plautii. Mechanistically, DAT promotes mTORC1-dependent activation and proliferation of intestinal stem cells, with concomitant engagement of the innate immune receptor STING required to mitigate metabolic stress and maintain an undifferentiated stem cell state independently of type-I interferon responses. Additionally, DAT can skew T cells towards an effector phenotype to modulate graft-versus-leukemia responses. Our data uncover DAT’s dual, tissue- and immune-modulating properties and underscore its potential in precision microbiome-based therapies to improve tissue regeneration and minimize immune-mediated side effects.
CRIS-Team Scopus Importer:2025-10-31

Tissue-adapted Tregs harness inflammatory signals to promote intestinal repair from therapy-related injury - Fischer, Julius C.; Göttert, Sascha; Giller, Maximilian; Heinrich, Paul; Fan, Kaiji; Khalid, Omer; Walther, Caroline N.; Drießlein, Maria; Nefzger, Sophie M.; Eisenkolb, Gabriel; Timnik, Vincent R.; Jarosch, Sebastian; et al. (Signal Transduction and Targeted Therapy, 2025)
Intestinal stem cells (ISCs) promote tissue repair after genotoxic or immune-mediated injury. However, ISCs are particularly sensitive to various stressors and primary targets of overwhelming immune responses, such as interferon γ (IFNγ)-mediated killing. In mouse models of radiation therapy-induced gut damage and in biopsies from patients who underwent allogeneic hematopoietic stem cell transplantation, we observed IFNγ expression by intestinal Treg cells. Treg cells leverage combined IFNγ and interleukin 10 (IL-10) stimulation of ISCs to nurture the growth of intestinal organoids through the activation of the mTORC1 and Myc pathways. Similarly, Treg cells or the combined addition of recombinant IFNγ and IL-10 promoted the regeneration of organoids after irradiation, and both cytokines were essential for ensuring epithelial regeneration following acute intestinal tissue injury in vivo. The exposure of organoids to growth factor-free culture conditions revealed distinct EGF-like properties of IFNγ and Wnt-like properties of IL-10. While IFNγ rapidly induced epithelial proliferation, it depleted the pool of ISCs in vitro. Only the combination of IFNγ and IL-10 led to epithelial proliferation and organoid growth while simultaneously ensuring ISC maintenance over time. Our results reveal a context-dependent role of inflammatory signaling in ISCs, through which Treg cells promote epithelial repair following therapy-induced injury.
CRIS-Team Scopus Importer:2025-12-05